2014
DOI: 10.1371/journal.pone.0090069
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Benefit of Bone Marrow–Derived Endothelial Progenitor Cell Transplantation after Experimental Aneurysm Embolization with Coil in Rats

Abstract: Aneurysm embolization with coil is now widely used clinically. However, the recurrence of aneurysms after embolization has always plagued neurosurgeons because the endothelial layer of the aneurysm neck loses its integrity after being embolized by coil. Bone marrow–derived endothelial progenitor cells (BM-EPCs) could be incorporated into injured endothelium and differentiate into mature endothelial cells during vascular repairing processes. The aim of our study is to explore the effects of BM-EPCs on aneurysm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Our previous study demonstrated the effect of bone marrow-derived EPCs in aneurysm neck endothelialization. 30 In the present study, we further demonstrated that the numbers of circulating EPCs increased in the rosuvastatin-treated rats, and more KDR+ cells adhered to the endothelial layer in the aneurysm neck (Fig. 3), indicating that rosuvastatin could promote EPC attachment to the aneurysm neck.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our previous study demonstrated the effect of bone marrow-derived EPCs in aneurysm neck endothelialization. 30 In the present study, we further demonstrated that the numbers of circulating EPCs increased in the rosuvastatin-treated rats, and more KDR+ cells adhered to the endothelial layer in the aneurysm neck (Fig. 3), indicating that rosuvastatin could promote EPC attachment to the aneurysm neck.…”
Section: Discussionsupporting
confidence: 74%
“…1 In addition, we have previously shown that bone marrow-derived EPCs play a crucial role in the closure and reconstruction of the aneurysm neck after coil embolization. 30 EPCs have demonstrated a robust effect on aneurysm neck endothelialization and the prevention of recurrence. Because EPCs are involved in the vascular repair and remodeling process, EPC-mediated therapy has been proposed as a potential treatment for vascular disease.…”
mentioning
confidence: 99%
“…In this study, bone marrow derived endothelial progenitor cells were labeled and transfused following aneurysm embolization. Zhang et al demonstrated that the labeled cells accumulated at the aneurysm neck accelerating repair and remodeling of the neck 63 .…”
Section: Application Of Biological Findingsmentioning
confidence: 99%
“…There is a growing interest in using circulating EPCs in clinical trials for ischemia, stroke, and vascular injury [24][25][26][27]. Our previous study [16] also showed that bone marrow-derived EPCs play a crucial role in the closure and reconstruction of the aneurysm neck orifice after aneurysm coiling.…”
Section: Discussionmentioning
confidence: 89%
“…Adult Sprague-Dawley rats (150-200 g) were used in the experiments (Slac Laboratory Animal, Shanghai, China, http://english.sibs.cas.cn/rs/fs/shanghailaboratoryanimalcentercas). The coiled AN model was prepared as previously reported [16]. The AN-EPO group was administered 1.5 mg/kg Recombinant Rat EPO (R&D Systems, Minneapolis, MN, https://www.rndsystems.com) injected subcutaneously, and the AN group was given an equal amount of saline subcutaneously.…”
Section: Methodsmentioning
confidence: 99%